Struktur Komunitas Makrozoobenthos di Ekosistem Mangrove Pulau Serangan Bali - I Ketut Dedi Ariawan; I Gusti Bagus Sila Dharma; Elok Faiqoh (Fakultas Kelautan dan Perikanan Universitas Udayana, 2021)
Macrozoobentos are organisms that live at the base of the water (Epifauna) or in the substrate (Infauna) with a size greater than 1 mm. Macrozoobenthos play an important role in the process of decomposition of organic matter in the sediment in the mangrove ecosystem. This research was conducted in August 2018 in the mangrove areas of Serangan Island, Bali. This research has purpose to know the structure of the Macrozoobenthos community in the mangrove ecosystem. It using a purposive sampling method, which consists of 2 stations, located in the north (adjacent TPA Suwung) as station 1 and on the south (directly facing the sea) as station 2. Each station consists of 5 substations with the distance between the substations adjusted to the condition of the existing mangrove community and each substation has 3 plots with a distance between the plot 10 m. The transect is drawn towards the sea for 50 m. The results obtained at station 2 had higher abundance of macrozoobenthos than Station 1, his shows the condition of the substrate at station 2 it supportive for the survival of macrozoobenthos organisms. The difference in the substrate in each station is thought to be one of the factors that influence the difference in macrozoobenthos density. At stations 1 and 2 have medium diversity, high Eveness and low dominance. This shows that the macrozoobenthos community in the mangrove ecosystem in the north and south of Serangan Island is in a stable condition but if the environment experiences a change, the change will affect the structure of the macrozoobenthos community in the ecosystem environment so that the value of species diversity is at a medium level.